Design-Construction Interface Problems in Sustainable Construction Projects in the UAE - Al Qasem, Dana (2023)
A Master of Science thesis in Construction Management by Dana Al Qasem entitled, “Design-Construction Interface Problems in Sustainable Construction Projects in the UAE”, submitted in November 2023. Thesis advisor is Dr. Sameh El-Sayegh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).